Local Strain Rate and Curvature Dependences of Scalar Dissipation Rate Transport in Turbulent Premixed Flames: A Direct Numerical Simulation Analysis. (3rd April 2014) - Gao, Y.; Chakraborty, N.; Swaminathan, N.
Abstract : The statistical behaviours of the instantaneous scalar dissipation rateN c of reaction progress variablec in turbulent premixed flames have been analysed based on three-dimensional direct numerical simulation data of freely propagating statistically planar flame and V-flame configurations with different turbulent Reynolds numberRe t . The statistical behaviours ofN c and different terms of its transport equation for planar and V-flames are found to be qualitatively similar. The mean contribution of the density-variation termT 1 is positive, whereas the molecular dissipation term( - D 2 ) acts as a leading order sink. The mean contribution of the strain rate termT 2 is predominantly negative for the cases considered here. The mean reaction rate contributionT 3 is positive (negative) towards the unburned (burned) gas side of the flame, whereas the mean contribution of the diffusivity gradient term( D ) assumes negative (positive) values towards the unburned (burned) gas side. The local statistical behaviours ofN c, T 1, T 2, T 3, ( - D 2 ), andf ( D ) have been analysed in terms of their marginal probability density functions (pdfs) and their joint pdfs with local tangential strain ratea T and curvaturek m . Detailed physical explanations have been provided for the observed behaviour.